Incorporación del uso tecnológico en la política pública de seguridad ciudadana en Medellín (2022)
This exploratory article seeks to answer the following questions: how has the use of technology been gaining relevance in public policies on citizen security in Medellín? What is the reason for its importance for security institutions? Likewise, this article seeks to analyze the incorporation of technological use in Medellín's security policy as a transversal element; this through an interpretative proposal and triangulation of information, by means of which local government documents, journalistic notes and a couple of interviews were consulted. The information analyzed allowed us to observe a growing interest in the use of technology in the city, which is incorporated into public policies on citizen security, with the design of a more comprehensive city management model, while also pointing out some possible adverse effects of this technological use.